PERILAKU PROFESIONAL TENAGA KESEHATAN DAERAH PESISIR PADA PELAYANAN KESEHATAN PRIMER WILAYAH PUSKESMAS ALAI KABUPATEN KEPULAUAN MERANTI TAHUN 2014 - Yolanda Nurliza; Dedi Afandi; Fifia Chandra (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
The professional behaviors is a vision of healthy Indonesian in improving the health services, therefore the medical-care need to improve their professional behaviors. The aim of this research was to describe the professional behaviors of the healthcare medical-care that assessed based on the six elements of professionalism. The success of the effort of the health services is not separated from the professional behaviors of the medical-care themselves. This research used exploration method with a qualitative approach in six community health center’s staff selected by Snowball sampling. The data were collected by using interviews and recorded with an audio recorder. The results showed that all informants contain altruism, accountability, duty, honor and integrity, respect for others and one of the six informants did not contain excellence. Based on the results of this research, the value of altruism, accountability, duty, honor and integrity, excellence, respect for others in Puskesmas Alai Kabupaten Kepulauan Meranti staff can be seen from the statements and the attitude of the health workers everyday.Key word : professional behavior, health workers, altruism, accountability, duty, honor and integrity, excellence, respect for others